Silver Nanoparticles: Biomedical Applications and Future Perspectives - Ranjbar, Samira; Bakhtiari, Ameneh; Khosravi, Negin; Jafari Ashkavandi, Shima; Azamian, Fariba; Alijaniha , Mahfam; Karbalaee , Mojtaba (Journal of Composites and Compounds, 2024)
Abstract Silver nanoparticles (AgNPs) have garnered significant attention in the biomedical field due to their unique physicochemical properties and versatile applications. This review explores the remarkable potential of AgNPs in various biomedical applications, including their roles in antimicrobial activity, anticancer therapies, and wound healing. The exceptional properties of AgNPs, such as their high surface area-to-volume ratio and enhanced reactivity, contribute to their effectiveness in combating infections and promoting tissue regeneration. Recent advancements in synthesis methods, including green synthesis approaches, have further enhanced the biocompatibility and efficacy of AgNPs. We discuss synthesis and mechanisms of AgNPs. Additionally, we highlight the challenges associated with the biomedical application of AgNPs. Future perspectives are provided, focusing on optimizing synthesis techniques, improving safety profiles, and exploring novel applications in personalized medicine. This comprehensive overview underscores the transformative role of silver nanoparticles in modern healthcare and their potential to address critical health challenges.